Hypotension: an unusual presentation of vitamin B(12) deficiency, with complete recovery following cyanocobalamin therapy - Yousaf, Zohaib (BMJ Case Rep, 2019)
Vitamin B(12) deficiency and its sequelae are well described and reported, especially in vegetarians. However, its association with haemodynamic instability is not well identified. We report a case of a young man, previously healthy, presenting with fever, hypotension requiring vasopressors and pancytopenia. Extensive workup was unrevealing for possible infective, inflammatory or endocrine causes except for vitamin B(12) deficiency. Fever and haematological parameters stabilised after adequate supplementation of cyanocobalamin (vitamin B(12)).